Modelagem do impacto do manejo do sedimento sobre o nível trófico do Açude Tijuquinha - Lira, Camila Cristina Souza (2017)
The eutrophication process gradually damages the reservoirs of Ceará, not only qualitatively but also quantitatively. The RESED project – of which this work takes part – had as general objective to demonstrate that the reuse method of the sediment deposited in dams is an effective control technique for the trophic state improvement of the superficial reservoirs and also in the increase of the productivity in the small-scale agriculture. The objective of this research is to evaluate the impact of sediment removal on the trophic level of the reservoir. Therefore, it was necessary to use a mathematical model for its quick and practical answers compared to the project realization in practice. The chosen model was developed by Chapra (1997), in which he describes the balance of total phosphorus in water and sediments in order to simulate the interference that the sediment feedback causes in the body's trophic state water. In the initial stage, the spatial pattern of sedimentation was studied with the main purpose of identifying sediment deposition conditions and estimating the sedimentation area, which are fundamental information for the model usage and for the adoption of de-sanding measures and sediment management. Finally, from the use of the model, it can be concluded that the impact of the sediment on the trophic level of Tijuquinha, during 40 years of analysis, was around 6%, that is, when the sedimented portion is removed annually, only 6% of the analyzed period would go from a high trophic level to an acceptable trophic state. One of the factors that may have led to this small impact on the improvement of water quality was the small hydraulic detention time – a particular characteristic of Tijuquinha – thus not enough time for nutrient accumulation.